THE CONCEPT OF FAIR VALUE - Anna N. Petrova; Vera I. Bazhenova (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article discusses historic and present day approaches to the concept of fair value from the point of view of IFRS 13 provisions. History of the fair value development shows the continuous extension of its use in overseas countries. This trend is also observed today. The authors analyze problems connected with defining and methodology of calculating the fair value, investigate theoretical and practical issues dealing with establishing this type of assessment and offer ideas about the use of fair value in Russia.  They show obstacles to using this assessment and its advantages and disadvantages. The possibility to use fair value for all entities of accounting is considered.